A case of mixed dust pneumoconiosis with desquamative interstitial pneumonia-like reaction in an aluminum welder. (2017) - Iijima, Yuki; Bando, Masashi; Yamasawa, Hideaki; Moriyama, Hiroshi; Takemura, Tamiko; Niki, Toshiro; Sugiyama, Yukihiko
Abstract: A 60-year-old man presented with an 18-month history of gradually worsening cough and a 12-month history of dyspnea on exertion. High-resolution computed tomography showed bilateral uniform ground grass opacity in the lower lung fields, partially resolved by smoking cessation. A tentative diagnosis of desquamative interstitial pneumonia (DIP) was made. Video-assisted thoracic surgery was performed and pathological analysis showed peribronchiolar fibrosis with intra-alveolar macrophage infiltration. Elemental analysis detected aluminum and iron in the upper lobe and only iron in the lower lobe. Thus, a definitive diagnosis of mixed dust pneumoconiosis with DIP-like reaction was made. DIP-like reaction is known to be a reactive change caused by exposure to tobacco smoke as well as by inhalation of inorganic particles. Obtaining a detailed medical history including occupational and environmental risk factors is important to distinguish cases of DIP-like reaction due to exposure to inorganic particles from the usual cases related to smoking, and thus provide suitable treatment.